MULTI-SCALE CHANGE ANALYSIS OF SEA ICE EXTENT IN ARCTIC - X. Liu; H. Chen; T. Feng (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2018)
The extent of polar sea ice is one of the key parameters of cryosphere and polar environmental change, which plays an important role in the study of global climate change. In this paper, the monthly product of sea ice extent, recorded from 1979 to 2016, was selected to analysis the change characteristics in multi time scales, which are annual, seasonal and monthly. It is found that the sea ice in Arctic was melting continuously for past four decades. And the melting rate was accelerated significantly since 2000. Furthermore, the Arctic was divided into thirteen sub-regions, and the change mechanism of sub-regions was discussed. Different change trends for sub-regions in four seasons were presented. Four active sub-regions were found, and the periodical analysis with the method of wavelet analysis was further carried out. The results show that the changes in the four active regions are periodic and the change period is over 10 years during the period from 1979 to 2016.